The Effect of Interactional Justice on Work Engagement through Conscientiousness for Work - Gökhan Kerse; Atılhan Naktiyok (Journal of Economy Culture and Society)
This research examines the direct and indirect effects of interactional justice perception of employees in the manufacturing sector on their levels of work engagement. The research adopted the view of social exchange theory and tried to determine whether interactional justice affects work engagement through conscientiousness for work. Social exchange is an approach that suggests that employees feel obliged to pay for resources if the organization provides valuable resources to the employee. In the study, which considers the perspective of social change, it was thought that if managers in the organization exhibit fairly behavior toward the employees, the latter will respond with conscientiousness for work and exhibit work engagement behavior. In addition, the conscientiousness (mediator) was considered to be a job-related situation rather than a general personality trait. The data were obtained from 156 employees at a manufacturing firm operating in Turkey. In the study, exploratory and confirmatory factor analysis, correlation analysis, path analysis and structural equation modeling analysis were conducted. In the analyses, it was observed that the perception of interactional justice positively affects both conscientiousness for work and work engagement. The findings of the analysis also show that the effect of interactional justice on work engagement is partially mediated by conscientiousness for work. All findings are discussed from the perspective of the cultural context in Turkey.